2020
DOI: 10.3390/ma13122831
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Properties of Rubberized ECC Incorporating Nano Graphene Using Response Surface Methodology

Abstract: Engineered cementitious composite (ECC) was discovered as a new substitute of conventional concrete as it provides better results in terms of tensile strain, reaching beyond 3%. From then, more studies were done to partially replace crumb rubber with sand to achieve a more sustainable and eco-friendlier composite from the original ECC. However, the elastic modulus of ECC was noticeably degraded. This could bring potential unseen dangerous consequences as the fatigue might happen at any time without any sign. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…This study dealt with the various combinations of dosages of NS, along with the SAP particles. The addition of SAP and nano-silica particles seemed to require more water for its binding, along with the hydration of cement, and an increase in the dosages of SAP and NS increased the water requirement, which is similar to the results of other NS studies reported by many researchers worldwide [50][51][52][53]. The mix M3 and M7 (having 1% NS significantly) seemed to have more compressive strength comparatively.…”
Section: Microstructural Characteristicssupporting
confidence: 85%
“…This study dealt with the various combinations of dosages of NS, along with the SAP particles. The addition of SAP and nano-silica particles seemed to require more water for its binding, along with the hydration of cement, and an increase in the dosages of SAP and NS increased the water requirement, which is similar to the results of other NS studies reported by many researchers worldwide [50][51][52][53]. The mix M3 and M7 (having 1% NS significantly) seemed to have more compressive strength comparatively.…”
Section: Microstructural Characteristicssupporting
confidence: 85%
“…There was a 19.2% increase in the compressive strength between a mix having 0.01% GO and that with 0.05% GO at a 10% CR replacement level. Similarly, Hau Hong et al [ 8 ] reported a 14% and 48% increase in the compressive strength and modulus of elasticity between a mix having 0.01% GO content and one with 0.05% GO, both at 10% CR replacement levels. This is due to the GO’s high reactivity, which speeds up the hydration reaction, resulting in increased calcium-silica-hydrate (C-S-H) gel formation and the pore-filling effect, which densifies the microstructure of the composite.…”
Section: Introductionmentioning
confidence: 90%
“…This behavior is attributed to the composite’s ability to develop and propagate saturated steady-state microcracks with a width of less than 100 μm. It is achieved by utilizing the micromechanics principles in the design of the composite to modify the interaction of the cement matrix, polymeric fibers, and their interface [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, pozzolanic activity could be increased through the packing influence, where LOI content reduced the chemical structure, particularly that of SOi 2 , from 69.02% to 59.17% [45]. In addition, a high pozzolanic activity could be obtained through a decrease in Ca(OH) 2 , MgO, and SO 3 [33,[91][92][93][94].…”
Section: Effect the Degree Of Fineness Of Pofa On The Blended Cement Pastementioning
confidence: 99%